2007
DOI: 10.1007/s00101-007-1191-z
|View full text |Cite
|
Sign up to set email alerts
|

Intoxikation mit einem trizyklischen Antidepressivum

Abstract: A 48-year-old woman with a major depression and treatment with doxepin was found comatose in her flat. Her son last saw her 48 h prior to being found. On arrival of the emergency physician, she presented a generalized seizure. The patient underwent endotracheal intubation and mechanical ventilation due to respiratory insufficiency and severe cyanosis. Empty packages of tablets (doxepin ca. 4000 mg and zolpidem 100 mg) were found in the flat. On hospital admission the doxepin blood concentration was 1.2 microg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Our results showed that tricyclic antidepressants are high-risk medicines for prisoners choosing to take an overdose. Overdosing on tricyclic antidepressants is generally quite common among patients being treated with these medications (Dianat et al, 2010; Sakka, Kuethe, & Hüttemann, 2007; Sinyor, Howlett, Cheung, & Schaffer, 2012). Regarding overdoses in prisoners, only a few other studies report individual cases of suicide by intoxication (Joukamaa, 1997; White et al, 2002; Wobeser et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that tricyclic antidepressants are high-risk medicines for prisoners choosing to take an overdose. Overdosing on tricyclic antidepressants is generally quite common among patients being treated with these medications (Dianat et al, 2010; Sakka, Kuethe, & Hüttemann, 2007; Sinyor, Howlett, Cheung, & Schaffer, 2012). Regarding overdoses in prisoners, only a few other studies report individual cases of suicide by intoxication (Joukamaa, 1997; White et al, 2002; Wobeser et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the application of ECTRs, even if they are usually considered generally safe, is not without cost and risks. In the present literature review, adverse effects of ECTRs, other than death, were reported: in subjects undergoing hemoperfusion, thrombocytopenia was reported in 25 patients, anemia in 12, bleeding or coagulation problems in 2, a clotting cartridge in 1, hypotension in 2, hypocalcemia in 5, and pulmonary edema in 1 . Peritoneal dialysis‐related peritonitis was reported in one patient, hyperglycemia in three cases, and hypothermia in one .…”
Section: Recommendationsmentioning
confidence: 78%
“…From the initial 1312 studies obtained, 77 studies met the inclusion criteria, including 1 observational study , 5 animal studies , 4 in vitro studies , 4 pharmacokinetic (PK) studies , and 63 case reports , 39 of which had sufficient toxicokinetic (TK) data. In total, 108 patients were included for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Liegt der Ingestionszeitpunkt nur sehr kurz zurück, kann in Ausnahmefäl-len eine Giftelimination mittels Magenspülung erwogen werden. Sekundäre Gifteliminationsverfahren werden in ihrer Effektivität kontrovers beurteilt [8,9]. Eine Hämoperfusion kann in Betracht gezogen werden (Übersicht unter [9]).…”
Section: Ekg-befundunclassified